La ingeniería química pilar multidisciplinario en diversas industrias. - Flores Murillo, Carlos Rene; Ochoa Celi, Joaquín Alejandro; Santamaría Robles, Lissette Beatriz (Editorial Grupo AEA, 2026)
The book takes us to explore the origins of chemical engineering and how it has evolved over time from a descriptive discipline to a more scientific and abstract one. It presents the structure and objectives of engineering today, as well as its growing importance in different industrial sectors and the trends that will mark its future. It also focuses on chemical processes, analyzing their current state and the prospects we have, with a special emphasis on their environmental impact and the need to use energy resources more responsibly. As we progress, the book introduces key terms to understand the basic operations in this area, classifying them in different ways and explaining the concept of design variable with clear examples. To facilitate understanding, at the end there is a summary table highlighting the most relevant objectives. In addition, it highlights the importance of innovation and technological process in chemical engineering to face global challenges, exploring advances in sustainability, biotechnology, nanotechnology, digitalization and continuing education. All this is fundamental to train chemical engineers who know how to manage resources and industrial processes effectively